[PP.16.03] COMPARISON OF UNATTENDED BLOOD PRESSURE MEASUREMENT (SPRINT METHOD) WITH OFFICE, 24H AMBULATORY AND CENTRAL BLOOD PRESSURE MEASUREMENTS IN HYPERTENSIVE PATIENTS. (September 2017) - Polonia, J.; Abreu, S.; Baptista, C.; Silva, J.; Barbosa, L.
Abstract : Objective: It has been discussed how unattended blood pressure (BP) measurement as done in SPRINT study correlates with other forms of BP evaluation which have been shown to be highly predictive of cardiovascular outcome. Figure. No caption available. Design and method: Study was done in a single centre for 3 months in 2016 and involved 118 consecutive hypertensive patients (60 female, ageing 56+17years, BMI 27+4 Kg/m 2 ) who were scheduled to carry out a 24 h ambulatory BP monitoring (ABPM) and who, in the interval of 48 hours that include ABPM, were also submitted to evaluation of casual BP (average 3 measurements), to an unattended 3 BP measurements separated by 2 minutes with a preprogrammed device (OMRON M10-IT), and to measurement of central BP from the aortic wave form (SphygmoCor). Results: As shown in table the difference casual-unattended SBP was remarkable. Also, it persisted (14–16 mmHg) along the tertiles of distribution of unattended SBP, whereas the differences of 24 h SBP, daytime BP and central SBP minus unattended of SBP significantly decreased from the lower to the upper tertiles. Conclusions: Along all the range of values, the unattended BP measurement significantly underestimate by 16/5 mmHg the BP values recorded in office thereby being more close to the 24 h and central (SBP) and to daytime (DBP) values. This must be considered when risk stratification is based on BP targets taken from unattended measurements.